Active living in later life: An overview of aging studies in hospitality and tourism journals. (February 2016) - Hung, Kam; Lu, Jiaying
Abstract: The most rapid growth of the aged population is predicted to occur after 2010, at which baby boomers would reach the age of 65. Here, a thorough review of past aging studies has been conducted and an overview on the progress of aging studies in six top journals in the tourism and hospitality fields over a three-decade period (1984–2013) is presented. A content analysis of 52 aging-related articles in the fields of hospitality and tourism identifies the research and methodological trends in aging studies in said fields. Significant study trends and possible exploration gaps are also discussed to raise awareness for future research.